PENINGKATAN HASIL BELAJAR MATEMATIKA MATERIPENJUMLAHAN DAN PENGURANGAN MELALUI PENGGUNAAN MEDIA WORDWALL PADA SISWA KELAS 1 SD NEGERI 007 SUNGAI PINANG TAHUN PEMBELAJARAN 2024/2025 - gustin indah lestari; Iksam; Muhammad Ramli Buhari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of grade 1 students of SD Negeri 007 Sungai Pinang, especially in addition and subtraction materials, which encouraged this researcher. The purpose of this study is to improve student learning outcomes through the use of wordwall learning media. This research is a classroom action research (CAR) which is carried out in three cycles, with each cycle consisting of three meetings. Each cycle goes through several stages, namely planning, implementation, observation and reflection. The research subjects were 31 students, with the object of this research being the improvement of learning outcomes using wordwall media. This data collection technique uses percentage, learning outcome completion, average value, and score as well as improvement of student learning outcomes. The results of the study showed that wordwall media succeeded in improving student learning outcomes. The average student score increased from 53 in the pre-cycle with a completion percentage of 13%, to 74 in cycle I with a completion percentage of 57%, then to 91 in cycle II with a completion percentage of 87%.